2005
DOI: 10.1158/0008-5472.can-04-3877
|View full text |Cite
|
Sign up to set email alerts
|

The Proinflammatory Cytokine Interleukin 1β and Hypoxia Cooperatively Induce the Expression of Adrenomedullin in Ovarian Carcinoma Cells through Hypoxia Inducible Factor 1 Activation

Abstract: Adrenomedullin (ADM) is a potent hypotensive peptide produced by macrophages and endothelial cells during ischemia and sepsis. The molecular mechanisms that control ADM gene expression in tumor cells are still poorly defined. It is known, however, that hypoxia potently increases ADM expression by activation of the transcription factor complex hypoxia inducible factor 1 (HIF-1). Proinflammatory cytokines produced by tumor invading macrophages likewise activate expression of ADM. Herein, we show that apart from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
63
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 55 publications
5
63
0
1
Order By: Relevance
“…In the absence of oxygen, hydroxylation of HIF-1␣ is inhibited and HIF-1␣ is no longer degraded and accumulates in the nucleus to regulate the cellular response to hypoxia. Apart from this hypoxic HIF-1 activation, several publications during the last years reported that HIF-1␣ is regulated independently of hypoxia (6,11,24). Especially under conditions of inflammation, increased HIF-1␣ accumulation followed by activation of HIF-1 target genes under nonhypoxic conditions have been described (25,26).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the absence of oxygen, hydroxylation of HIF-1␣ is inhibited and HIF-1␣ is no longer degraded and accumulates in the nucleus to regulate the cellular response to hypoxia. Apart from this hypoxic HIF-1 activation, several publications during the last years reported that HIF-1␣ is regulated independently of hypoxia (6,11,24). Especially under conditions of inflammation, increased HIF-1␣ accumulation followed by activation of HIF-1 target genes under nonhypoxic conditions have been described (25,26).…”
Section: Discussionmentioning
confidence: 98%
“…However, it is commonly accepted that endotoxin tolerance leads to an impaired release of proinflammatory cytokines like IL-1␤ and TNF-␣ from monocytes and macrophages after LPS stimulation (1). These cytokines have been shown to induce the accumulation and activation of the transcription factor complex hypoxia-inducible factor 1 (HIF-1) 3 independently of hypoxia (5)(6)(7). HIF-1 belongs to a family of heterodimeric transcription factors that regulates the expression of genes involved in angiogenesis, oxygen transport, glucose metabolism, and vascular tone (8).…”
mentioning
confidence: 99%
“…Several nonhypoxic stimuli have been shown to strongly increase HIF-1 activation under normoxic conditions in a cell-specific manner, thereby increasing the transcription of genes that are primarily induced by hypoxia. These stimulants include cytokines such as IFN-␥, IL-1␤, and TNF (Albina et al, 2001;Haddad and Land, 2001;Jung et al, 2003aJung et al, , 2003bScharte et al, 2003;Frede et al, 2005;Varney et al, 2005), growth factors (Feldser et al, 1999;Gorlach et al, 2001;Shih and Claffey, 2001;Tacchini et al, 2001;Fukuda et al, 2002), and hormones such as thrombin, thrombopoietin, and angiotensin (Gorlach et al, 2001;Page et al, 2002;Kirito et al, 2005). Most of these studies report induction of HIF-1␣ through an increase in protein levels rather than increased levels of HIF-1␣ mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…At higher oxygen tension, the HIF-1α subunit of HIF-1 is degraded due to the activity of prolyl hydroxylase enzymes [3], while in hypoxia HIF-1α is stabilized and translocated into the nucleus [4]. In addition, HIF-1α expression can be upregulated even under normoxic conditions by IL-4 [5], TNF-α [6], IL-1 [7], and other cytokines. The TCR-mediated activation of T cells in mice results in a selective induction of the alternatively spliced mRNA isoform I.1 of HIF-1α [8].…”
Section: Introductionmentioning
confidence: 99%